2023
DOI: 10.3389/fpsyg.2023.1154502
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Russian-Ukrainian war on the mental health of Italian people after 2 years of the pandemic: risk and protective factors as moderators

Abstract: ObjectiveThis contribution aimed at investigating the moderating role of risk (e.g., the negative influence of COVID-19 on mental health) and protective (e.g., post-traumatic growth) factors on the relationship between the concern for war and stress and anxiety/depression levels among Italian people.MethodsA questionnaire that included sociodemographic characteristics, the Perceived Stress Scale (PSS-4), the Patient Health Questionnaire (PHQ-4), the Brief Resilience Scale (BRS), the Post-Traumatic Growth Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…The present study investigated the indirect psychological impact of war on mental health in a sample of Italian young adults considering the direct influence of Fear of War on psychological distress on the one hand and, on the other, the mediating effect that Future Anxiety and Intolerance of Uncertainty play in this relationship. The findings suggest that Fear of War positively predicts Stress, Anxiety, and Depression, and the results are in line with recent studies conducted in contexts that are not directly involved in warfare [48,49], including some Italian ones that exclusively explore the general impact of war without using the specific construct of Fear of War [51,52]. Results of parallel mediation models show that Fear of War is increasing Future Anxiety and Intolerance of Uncertainty levels, significantly affecting psychological distress, and potentiating the impact of Fear of War on Stress, Anxiety, and Depression with a significant indirect effect.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study investigated the indirect psychological impact of war on mental health in a sample of Italian young adults considering the direct influence of Fear of War on psychological distress on the one hand and, on the other, the mediating effect that Future Anxiety and Intolerance of Uncertainty play in this relationship. The findings suggest that Fear of War positively predicts Stress, Anxiety, and Depression, and the results are in line with recent studies conducted in contexts that are not directly involved in warfare [48,49], including some Italian ones that exclusively explore the general impact of war without using the specific construct of Fear of War [51,52]. Results of parallel mediation models show that Fear of War is increasing Future Anxiety and Intolerance of Uncertainty levels, significantly affecting psychological distress, and potentiating the impact of Fear of War on Stress, Anxiety, and Depression with a significant indirect effect.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have highlighted how the Russian-Ukrainian war is generating repercussions on mental health even in the Italian context, fueling, on the one hand, specific concerns associated with the indirect consequences of the war on the economic level and the cost of living [28,51] and, on the other, the levels of Stress, Anxiety, and Depression in the general population, already affected by the recent COVID-19 pandemic [52]. Nonetheless, the indirect psychological impact of war on mental health remains partly unexplored, particularly in young adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most participants reported anxieties such as the possibility of the war between Russia and Ukraine spreading to other European countries, or it being the cause of World War III or a nuclear risk. Previous studies focusing on the impact of the Russian–Ukrainian war on people’s mental health demonstrated a high experienced risk of nuclear war [ 31 ] and war-related concerns increasing stress, anxiety, and depression levels in populations not directly involved in the conflict [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In today's rapidly changing world, affected in recent years by several major crises such as the Covid-19 pandemic, the war in Ukraine and the related energy and cost of living crises, individuals are invariably exposed to various stressors. This commonly leads to increased experience of stress 1 3 . Defined as a state of threatened homeostasis following exposure to extrinsic or intrinsic adverse forces 4 , this stress can negatively affect daily functioning.…”
Section: Introductionmentioning
confidence: 99%